Biological vascular stent material and preparation method thereof
By introducing nickel-titanium composite powder and exosomes into the vascular stent material and preparing the composite material by using coaxial electrospinning technology, the problems of low porosity, poor elongation and support of existing vascular stent materials are solved, and the problems of low elongation and poor support are achieved. The effect of improving porosity, elongation and support strength of the material is enhanced.
Patent Information
- Application Number
- CN202411660806.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The existing vascular stent materials have problems such as low porosity, poor cell adhesion, poor elongation and support, which lead to easy damage during use.
By using polylactic acid-polyvinyl alcohol emulsion with nickel-titanium composite powder added as the cortical spinning liquid, combined with exosome-containing sodium alginate solution as the core spinning liquid, the composite material was prepared by coaxial electrospinning technology. And a post-treatment process was carried out to obtain biological vascular stent material.
It effectively improves the porosity of the material, increases the elongation and support of the vascular stent, and improves the adhesion and durability of the material.
Smart Images

Figure BDA0005143289940000101 
Figure BDA0005143289940000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a biological blood vessel stent material and a preparation method thereof. Background Art
[0002] Cardiovascular disease is a disease related to the heart and blood vessels. In addition to drug treatments such as vasodilators or anticoagulants, surgery and transplantation are usually the ideal treatment options for patients with pathological conditions. Vascular grafts are generally used to replace or bypass diseased blood vessels. Biological vascular scaffold materials are often used in surgical operations, such as vascular stents and intestinal stents that provide support. In addition, they also include artificial bone scaffolds and artificial organ scaffolds that serve as carriers of nutrients and provide a certain size structure. Exosomes are small vesicles secreted by cells, with a diameter usually between 30 and 150 nanometers. They play an important role in intercellular communication, material transport, and signal transmission, and have broad application prospects.
[0003] A Chinese patent (publication number CN113274561B) discloses a medical vascular stent material, which is a double-layer composite material made of silk protein powder, polylactic acid, polycaprolactone, chitosan and recombinant human collagen as raw materials, through coaxial electrospinning, ammonia and warm water soaking in sequence; the polymer stent composite material prepared by the invention has excellent structural stability, does not fall off during use, has good biomechanical properties and cell compatibility, and can effectively form support when used for vascular stents. However, the vascular stent materials in the prior art still have problems such as low porosity leading to poor cell adhesion, poor elongation and support leading to easy damage during use, which limits the further use of vascular stent materials.
[0004] Therefore, how to combine different stent materials, introduce modified components and active ingredients such as exosomes, prepare biological vascular stent materials by electrospinning, effectively improve the porosity of the material, and increase the elongation and supporting force of the stent has become a direction that needs to be tackled. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a biological vascular stent material and a preparation method thereof, aiming to solve the problems of low porosity of vascular stent materials in the prior art resulting in poor cell adhesion, poor elongation and supporting strength resulting in easy damage during use, etc.
[0006] The present invention uses polylactic acid-polyvinyl alcohol emulsion added with nickel-titanium composite powder as the cortex spinning solution, and sodium alginate solution containing exosomes as the core spinning solution, prepares the composite material by coaxial electrospinning technology, and obtains the biological vascular stent material in conjunction with a post-treatment process, effectively improving the porosity of the material, while increasing the elongation and supporting force of the vascular stent.
[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0008] The first aspect of the present invention provides a method for preparing a biological vascular stent material, comprising the following steps:
[0009] Step S1: adding 5 to 8 parts of polylactic acid to 100 to 120 parts of dichloromethane by weight, and magnetically stirring at room temperature for 4 to 6 hours to obtain a polylactic acid solution; adding 1 to 3 parts of polyvinyl alcohol to 100 to 120 parts of deionized water, and magnetically stirring at 60 to 70° C. for 2 to 4 hours, and cooling to room temperature to obtain a polyvinyl alcohol solution; mixing 40 to 45 parts of the polylactic acid solution and 10 to 15 parts of the polyvinyl alcohol solution, and then adding 0.1 to 0.3 parts of an emulsifier and 2 to 4 parts of a nickel-titanium composite powder, and high-speed emulsification at a rotation speed of 5000 to 7000 r / min for 10 to 20 minutes to obtain a polylactic acid-polyvinyl alcohol emulsion;
[0010] Step S2: by weight, 6 to 12 parts of sodium alginate are added to 100 to 120 parts of deionized water, stirred at 45 to 55° C. for 2 to 4 hours, and then 1 to 3 parts of exosomes are added and mixed evenly to obtain a sodium alginate solution containing exosomes;
[0011] Step S3: using the polylactic acid-polyvinyl alcohol emulsion as a skin layer spinning solution and the sodium alginate solution containing exosomes as a core layer spinning solution, and obtaining a composite material by coaxial electrospinning;
[0012] Step S4: vacuum-drying the composite material and then performing post-processing to obtain a biological vascular stent material.
[0013] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0014] As a preferred technical solution of the present invention, the emulsifier is selected from any one of Span 80, Span 20 and Tween 80, or a combination of at least two of them.
[0015] Polylactic acid and polyvinyl alcohol are formulated into an emulsion through an emulsifier and used as the cortex spinning solution. During the electrospinning process, the cortex spinning solution forms a composite cortex structure with polylactic acid fibers as the main body and polyvinyl alcohol distributed on the polylactic acid fibers. At the same time, after post-treatment, the polyvinyl alcohol will dissolve in water, thereby forming holes in the composite cortex, effectively improving the porosity of the biological vascular stent material.
[0016] As a preferred technical solution of the present invention, the preparation method of the nickel-titanium composite powder described in step S1 includes: in parts by weight, 30 to 35 parts of a sulfuric acid solution with a molar concentration of 18 mol / L and 10 to 15 parts of a nitric acid solution with a molar concentration of 7.0 mol / L are mixed evenly, and then 5 to 10 parts of carbon nanotubes are added, and acidification treatment is performed at 80 to 90° C. for 8 to 10 hours. After acidification, the upper clear liquid is removed by centrifugation, and then the pH value of the lower liquid is adjusted to neutral with deionized water, and then 0.1 to 0.3 parts of hexadecyltrimethylammonium bromide is added for ultrasonic oscillation for 2 to 4 hours to obtain a carbon nanotube suspension; 30 to 40 parts of porous nickel-titanium powder are added to 40 to 50 parts of the carbon nanotube suspension and stirred for 30 to 40 minutes, and then allowed to stand for adsorption, vacuum filtered, and dried to obtain a nickel-titanium composite powder.
[0017] Preferably, the conditions for the static adsorption are: temperature of 50-60° C. and time of 40-60 min.
[0018] As a preferred technical solution of the present invention, the preparation method of the porous nickel-titanium powder includes: mixing 140 to 145 parts of nickel powder and 90 to 95 parts of titanium powder by weight, and then pressing them into thin sheets, keeping the pressed thin sheets at 700 to 750°C for 3 to 4 hours, and cooling them to room temperature to obtain a nickel-titanium alloy sintered material; placing 200 to 240 parts of the nickel-titanium alloy sintered material into a ball mill, adding an ethanol solution with a mass concentration of 80% and grinding for 10 to 12 hours, and drying them at 105 to 110°C for 2 to 4 hours to obtain a porous nickel-titanium powder.
[0019] The porous nickel-titanium powder in the nickel-titanium composite powder improves the ductility of the vascular stent by refining the grains of the nickel-titanium alloy and optimizing the phase change behavior of the material. At the same time, the composite powder can absorb and disperse external forces, reduce local stress concentration in the material, and improve the elongation of the material. The acidified carbon nanotubes can increase the interface bonding strength with the polymer matrix, and combine to form a network structure to effectively disperse stress, thereby improving the elongation of the biological vascular stent material.
[0020] As a preferred technical solution of the present invention, the method for preparing exosomes includes: thawing the plasma in a water bath, centrifuging at room temperature for 20 to 25 minutes to remove residual debris, transferring the supernatant to a centrifuge tube, and storing it on ice to obtain a plasma sample; in parts by weight, adding 0.75 to 0.80 parts of phosphate buffer to 15 to 20 parts of the plasma sample and vortex mixing, then adding 0.45 to 0.50 parts of exosome extraction reagent and mixing evenly, standing at 4°C for 20 to 30 minutes, and then centrifuging for 5 to 10 minutes, removing the liquid to obtain the precipitate at the bottom of the tube, which is the exosome.
[0021] The sodium alginate solution containing exosomes is used as the core layer component of the composite material. During post-processing of the composite material, the polyvinyl alcohol in the cortex will dissolve in the aqueous solution and form holes on the cortex, exposing the sodium alginate in the core layer. The post-processing solution contains calcium ions, which can form cross-linking points with the carboxyl groups of sodium alginate, thereby quickly combining and forming a three-dimensional network structure, significantly improving the supporting capacity of the vascular stent material.
[0022] Preferably, the conditions for the coaxial electrospinning in step S3 are: voltage of 16-22 kV, temperature of 25-30° C., humidity of 40-60%, and receiving distance of 20-25 cm.
[0023] As a preferred technical solution of the present invention, the post-treatment in step S4 includes: soaking the composite material in a calcium salt solution with a mass concentration of 2-4% for 30-60 minutes, washing with deionized water after soaking, and obtaining a biological vascular stent material after drying.
[0024] Preferably, the calcium salt is selected from any one or a combination of at least two of calcium chloride, calcium lactate and calcium L-gluconate.
[0025] The second aspect of the present invention provides a biological vascular stent material prepared by the method described in the first aspect.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention introduces exosomes into the biological vascular scaffold material. Due to the complexation of sodium alginate and calcium, the exosomes can be effectively retained in the biological vascular scaffold material. The exosomes can mediate intercellular communication between different types of cells in the body by transmitting signal molecules such as proteins, lipids, mRNA, and microRNAs, and act as signal transduction carriers between cells. The exosomes' contents are switched in this process, promoting cell proliferation, migration, differentiation, and antigen presentation.
[0028] (2) During the immersion treatment in the post-processing step of the present invention, the polyvinyl alcohol in the cortex will dissolve in water, thereby forming holes in the composite cortex, effectively increasing the porosity of the stent material; in addition, the nickel-titanium composite powder and polylactic acid together form a porous structure in the cortex, which together effectively improve the porosity of the biological vascular stent material.
[0029] (3) The post-treatment process of the present invention can promote sodium alginate and calcium ions to form a gel-like combination, which has good flexibility and can maintain good adaptability when the blood vessel is bent and expanded, thereby increasing the elongation of the vascular stent material; at the same time, the nickel-titanium composite powder is used to reduce the local stress concentration of the material, and the acidified carbon nanotubes are combined with the polymer to form a network structure, which synergistically increases the elongation of the biological vascular stent material.
[0030] (4) When the composite material of the present invention is post-treated, the polyvinyl alcohol in the cortex will dissolve in the aqueous solution and form holes in the cortex, exposing the sodium alginate in the core layer. The post-treated solution contains calcium ions, which can form cross-linking points with the carboxyl groups of sodium alginate, thereby quickly combining and forming a three-dimensional network structure, significantly improving the supporting force of the vascular stent material. DETAILED DESCRIPTION
[0031] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0032] The sources of some components in the embodiments and comparative examples are as follows:
[0033] Polylactic acid, product number 38534, was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0034] Dichloromethane, CAS No. 75-09-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0035] Polyvinyl alcohol, catalog number P21501218, was purchased from Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd.;
[0036] Span 80, catalog number PA82062, purchased from Shanghai Chuangsai Technology Co., Ltd.;
[0037] Span 20, item number PA81828, purchased from Shanghai Chuangsai Technology Co., Ltd.;
[0038] Tween 80, catalog number PA86332, was purchased from Shanghai Chuangsai Technology Co., Ltd.;
[0039] Nickel powder, item number W5, was purchased from Huizhou Tenghui Technology Co., Ltd.;
[0040] Titanium powder, product number M24934, was purchased from Shanghai Myrel Biochemical Technology Co., Ltd.;
[0041] Sulfuric acid, CAS No. 7664-93-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0042] Nitric acid, CAS No. 7697-37-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0043] Carbon nanotubes, product number MWNT-10, were purchased from Shenzhen Nanoport Co., Ltd.;
[0044] Hexadecyltrimethylammonium bromide, CAS number 57-09-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0045] Sodium alginate, product number S11053, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0046] Plasma, catalog number ABC-TC3386, was purchased from Beijing Bio Innovation Technology Co., Ltd.;
[0047] Exosome extraction reagent, catalog number 4484452, was purchased from Thermo Fisher Scientific;
[0048] Calcium chloride, CAS No. 10043-52-4, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0049] Calcium lactate, CAS No. 814-80-2, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0050] Calcium L-gluconate, CAS No. 152772-65-1, was purchased from Hubei Yangxin Pharmaceutical Technology Co., Ltd.
[0051] Preparation of nickel-titanium composite powder: (1) In parts by weight, 140 parts of nickel powder and 90 parts of titanium powder are mixed evenly and pressed into thin sheets. The pressed thin sheets are kept at 700°C for 4 hours and cooled to room temperature to obtain a nickel-titanium alloy sintered material; 230 parts of the nickel-titanium alloy sintered material are placed in a ball mill, an ethanol solution with a mass concentration of 80% is added, and the mixture is ground for 12 hours. The mixture is dried at 105°C for 4 hours to obtain a porous nickel-titanium powder. (2) In parts by weight, 30 parts of 18 mol / L sulfuric acid solution and 10 parts of 7.0 mol / L nitric acid solution were mixed evenly, and then 5 parts of carbon nanotubes were added, and the mixture was acidified at 90°C for 8 hours. After the acidification, the upper clear liquid was removed by centrifugation, and the pH value of the lower liquid was adjusted to neutral with deionized water, and then 0.1 parts of hexadecyltrimethylammonium bromide was added and ultrasonically oscillated for 2 to 4 hours to obtain a carbon nanotube suspension; 30 parts of porous nickel-titanium powder were added to 40 parts of the carbon nanotube suspension and stirred for 30 minutes, and then allowed to stand for adsorption (temperature 50°C, time 60 minutes), vacuum filtered, and dried to obtain a nickel-titanium composite powder.
[0052] Preparation of exosomes: thaw the plasma in a water bath, centrifuge at room temperature for 20 minutes to remove residual debris, transfer the supernatant to a centrifuge tube, and store it on ice to obtain a plasma sample; by weight, add 0.75 parts of phosphate buffer to 15 parts of the plasma sample and vortex mix, then add 0.45 parts of exosome extraction reagent and mix evenly, let stand at 4°C for 20 minutes, then centrifuge for 5 minutes, remove the liquid to obtain the precipitate at the bottom of the tube, which is the exosome.
[0053] Preparation of sodium alginate solution: By weight, 12 parts of sodium alginate were added to 120 parts of deionized water, and stirred at 55° C. for 2 hours to obtain a sodium alginate solution.
[0054] Example 1
[0055] This embodiment provides a method for preparing a biological vascular stent material, comprising the following steps:
[0056] Step S1: In parts by weight, 8 parts of polylactic acid are added to 120 parts of dichloromethane, and magnetically stirred at room temperature for 6 hours to obtain a polylactic acid solution; 3 parts of polyvinyl alcohol are added to 120 parts of deionized water, and magnetically stirred at 70° C. for 2 hours, and cooled to room temperature to obtain a polyvinyl alcohol solution; 45 parts of the polylactic acid solution and 15 parts of the polyvinyl alcohol solution are mixed, and then 0.3 parts of Span 80 and 4 parts of nickel-titanium composite powder are added, and high-speed emulsification is carried out at a speed of 7000 r / min for 10 minutes to obtain a polylactic acid-polyvinyl alcohol emulsion;
[0057] Step S2: by weight, 12 parts of sodium alginate were added to 120 parts of deionized water, stirred at 55° C. for 2 h, and then 3 parts of exosomes were added and mixed evenly to obtain a sodium alginate solution containing exosomes;
[0058] Step S3: using the polylactic acid-polyvinyl alcohol emulsion as the skin layer spinning solution and the sodium alginate solution containing exosomes as the core layer spinning solution, and obtaining a composite material by coaxial electrospinning; the conditions of the coaxial electrospinning are: voltage of 22 kV, temperature of 30° C., humidity of 40%, and receiving distance of 25 cm;
[0059] Step S4: soaking the composite material in a calcium chloride solution with a mass concentration of 4% for 30 minutes, washing with deionized water after soaking, and drying to obtain a biological vascular stent material.
[0060] Example 2
[0061] This embodiment provides a method for preparing a biological vascular stent material, comprising the following steps:
[0062] Step S1: In parts by weight, 5 parts of polylactic acid are added to 100 parts of dichloromethane, and magnetically stirred at room temperature for 4 hours to obtain a polylactic acid solution; 1 part of polyvinyl alcohol is added to 100 parts of deionized water, and magnetically stirred at 60-70° C. for 2 hours, and cooled to room temperature to obtain a polyvinyl alcohol solution; 40 parts of the polylactic acid solution and 10 parts of the polyvinyl alcohol solution are mixed, and then 0.1 parts of Span 20 and 2 parts of nickel-titanium composite powder are added, and high-speed emulsification is carried out at a speed of 5000 r / min for 20 minutes to obtain a polylactic acid-polyvinyl alcohol emulsion;
[0063] Step S2: by weight, 6 parts of sodium alginate were added to 100 parts of deionized water, stirred at 45° C. for 4 h, and then 1 part of exosomes were added and mixed evenly to obtain a sodium alginate solution containing exosomes;
[0064] Step S3: using the polylactic acid-polyvinyl alcohol emulsion as the skin layer spinning solution and the sodium alginate solution containing exosomes as the core layer spinning solution, and obtaining a composite material by coaxial electrospinning; the coaxial electrospinning conditions are: voltage of 16 kV, temperature of 25° C., humidity of 60%, and receiving distance of 20 cm;
[0065] Step S4: soaking the composite material in a calcium lactate solution with a mass concentration of 2% for 30 minutes, washing with deionized water after soaking, and drying to obtain a biological vascular stent material.
[0066] Example 3
[0067] This embodiment provides a method for preparing a biological vascular stent material, comprising the following steps:
[0068] Step S1: adding 6 parts of polylactic acid to 105 parts of dichloromethane by weight, and magnetically stirring at room temperature for 5 hours to obtain a polylactic acid solution; adding 2 parts of polyvinyl alcohol to 11 parts of deionized water, and magnetically stirring at 65° C. for 3 hours, and cooling to room temperature to obtain a polyvinyl alcohol solution; mixing 42 parts of the polylactic acid solution and 13 parts of the polyvinyl alcohol solution, and then adding 0.2 parts of Tween 80 and 3 parts of nickel-titanium composite powder, and high-speed emulsification at a speed of 6000 r / min for 15 minutes to obtain a polylactic acid-polyvinyl alcohol emulsion;
[0069] Step S2: by weight, 8 parts of sodium alginate were added to 110 parts of deionized water, stirred at 48° C. for 3 h, and then 2 parts of exosomes were added and mixed evenly to obtain a sodium alginate solution containing exosomes;
[0070] Step S3: using the polylactic acid-polyvinyl alcohol emulsion as the skin layer spinning solution and the sodium alginate solution containing exosomes as the core layer spinning solution, and obtaining a composite material by coaxial electrospinning; the coaxial electrospinning conditions are: voltage of 20 kV, temperature of 28° C., humidity of 50%, and receiving distance of 22 cm;
[0071] Step S4: soaking the composite material in a 3% L-calcium gluconate solution for 45 minutes, washing with deionized water after soaking, and drying to obtain a biological vascular stent material.
[0072] Comparative Example 1
[0073] This comparative example provides a method for preparing a biological vascular stent material, comprising the following steps:
[0074] Step S1: adding 8 parts of polylactic acid to 120 parts of dichloromethane by weight, and stirring under magnetic force at room temperature for 6 hours to obtain a polylactic acid solution;
[0075] Step S2: by weight, 12 parts of sodium alginate are added to 120 parts of deionized water, and stirred at 55° C. for 2 hours to obtain a sodium alginate solution;
[0076] Step S3: using the polylactic acid solution as the skin layer spinning solution and the sodium alginate solution as the core layer spinning solution to obtain a composite material by coaxial electrospinning; the conditions of the coaxial electrospinning are: voltage of 22 kV, temperature of 30° C., humidity of 40%, and receiving distance of 25 cm;
[0077] Step S4: soaking the composite material in a calcium chloride solution with a mass concentration of 4% for 30 minutes, washing with deionized water after soaking, and drying to obtain a biological vascular stent material.
[0078] Comparative Example 2
[0079] This comparative example provides a method for preparing a biological vascular stent material, which differs from comparative example 1 in that 4 parts of nickel-titanium composite powder are added to the cortex spinning solution.
[0080] Comparative Example 3
[0081] This comparative example provides a method for preparing a biological vascular stent material, which is different from Example 1 in that no nickel-titanium composite powder is added to the cortex spinning solution, and the core layer spinning solution uses a sodium alginate solution instead of a sodium alginate solution containing exosomes.
[0082] Comparative Example 4
[0083] This comparative example provides a method for preparing a biological vascular stent material, which is different from Example 1 in that the post-treatment process of step S4 is not performed.
[0084] Comparative Example 5
[0085] This comparative example provides a method for preparing a biological vascular stent material, which differs from Example 1 in that deionized water is used instead of calcium chloride solution for the post-treatment process.
[0086] The performance of the biological vascular stent material provided in the above embodiments and comparative examples was tested, and the testing method was as follows:
[0087] (1) Porosity test
[0088] The porosity is tested according to the requirements of "YY / T 1616-2018 Performance and Test Guide for Biomaterial Scaffolds for Tissue Engineering Medical Device Products".
[0089] (2) Elongation test
[0090] The elongation is tested with reference to the requirements of "YY / T 1616-2018 Performance and Test Guide for Biomaterial Scaffolds for Tissue Engineering Medical Device Products".
[0091] (3) Support force test
[0092] The supporting force is tested according to the requirements of "YY / T 1660-2019 Radial Load Test Method for Balloon-Expandable and Self-Expanding Vascular Stents".
[0093] The above performance test data is shown in Table 1.
[0094] Table 1 Performance test results
[0095]
[0096]
[0097] From the above content, it can be seen that the present invention uses polylactic acid-polyvinyl alcohol emulsion as the cortex spinning solution, uses sodium alginate solution containing exosomes as the core spinning solution, prepares the composite material by coaxial electrospinning technology, and cooperates with the post-treatment process to obtain the biological vascular stent material (Example 1 to Example 3), the porosity of the stent material is 72.38~74.18%, the elongation is 16.78~16.92%, and the supporting force is 3.28~3.34MPa.
[0098] Comparative Example 1 does not adopt the necessary technical solution of the present invention, resulting in its performance test being significantly worse than that of the embodiment, with a porosity of 51.84%, an elongation of 12.57%, and a support force of 2.52MPa. Compared with Comparative Example 1, if nickel-titanium composite powder is added to the cortex spinning solution, the elongation increases and the porosity increases (Comparative Example 2); compared with Example 1, if nickel-titanium composite powder is not added to the cortex spinning solution, and the core spinning solution uses sodium alginate solution instead of sodium alginate solution containing exosomes, the porosity becomes smaller, and the elongation decreases (Comparative Example 3); compared with Example 1, if the post-treatment process of step S4 is not performed, the porosity becomes smaller, the elongation decreases, and the support force decreases (Comparative Example 4); compared with Example 1, if deionized water is used instead of calcium chloride solution for post-treatment, the elongation decreases and the support force decreases (Comparative Example 5).
[0099] Polylactic acid-polyvinyl alcohol emulsion is used as the cortex spinning solution, and sodium alginate solution containing exosomes is used as the core spinning solution. The composite material is prepared by coaxial electrospinning technology, and the biological vascular stent material is obtained in conjunction with a post-processing process, which effectively improves the porosity of the material while increasing the elongation and supporting force of the vascular stent.
[0100] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a biological vascular stent material, characterized in that: The following steps are involved: Step S1: adding 5 to 8 parts of polylactic acid to 100 to 120 parts of dichloromethane by weight, and magnetically stirring at room temperature for 4 to 6 hours to obtain a polylactic acid solution; adding 1 to 3 parts of polyvinyl alcohol to 100 to 120 parts of deionized water, and magnetically stirring at 60 to 70° C. for 2 to 4 hours, and cooling to room temperature to obtain a polyvinyl alcohol solution; mixing 40 to 45 parts of the polylactic acid solution and 10 to 15 parts of the polyvinyl alcohol solution, and then adding 0.1 to 0.3 parts of an emulsifier and 2 to 4 parts of a nickel-titanium composite powder, and high-speed emulsification at a rotation speed of 5000 to 7000 r / min for 10 to 20 minutes to obtain a polylactic acid-polyvinyl alcohol emulsion; Step S2: by weight, 6 to 12 parts of sodium alginate are added to 100 to 120 parts of deionized water, stirred at 45 to 55° C. for 2 to 4 hours, and then 1 to 3 parts of exosomes are added and mixed evenly to obtain a sodium alginate solution containing exosomes; Step S3: using the polylactic acid-polyvinyl alcohol emulsion as a skin layer spinning solution and the sodium alginate solution containing exosomes as a core layer spinning solution, and obtaining a composite material by coaxial electrospinning; Step S4: vacuum-drying the composite material and then performing post-processing to obtain a biological vascular stent material.
2. The method for preparing a biological vascular stent material according to claim 1, characterized in that: In step S1, the emulsifier is selected from any one of Span 80, Span 20 and Tween 80, or a combination of at least two of them.
3. The method for preparing a biological vascular stent material according to claim 1, characterized in that: The preparation method of the nickel-titanium composite powder in step S1 includes: mixing 30 to 35 parts of a sulfuric acid solution with a molar concentration of 18 mol / L and 10 to 15 parts of a nitric acid solution with a molar concentration of 7.0 mol / L, by weight, and then adding 5 to 10 parts of carbon nanotubes, acidifying at 80 to 90° C. for 8 to 10 hours, centrifuging to remove the upper clear liquid after the acidification, and then adjusting the pH value of the lower liquid to neutral with deionized water, and then adding 0.1 to 0.3 parts of hexadecyltrimethylammonium bromide for ultrasonic oscillation for 2 to 4 hours to obtain a carbon nanotube suspension; adding 30 to 40 parts of porous nickel-titanium powder to 40 to 50 parts of the carbon nanotube suspension and stirring for 30 to 40 minutes, and then standing for adsorption, vacuum filtering, and drying to obtain a nickel-titanium composite powder.
4. The method for preparing a biological vascular stent material according to claim 3, characterized in that: The conditions for the static adsorption are: a temperature of 50 to 60° C. and a time of 40 to 60 minutes.
5. The method for preparing a biological vascular stent material according to claim 3, characterized in that: The preparation method of the porous nickel-titanium powder comprises: mixing 140 to 145 parts of nickel powder and 90 to 95 parts of titanium powder by weight, and pressing the mixture into thin slices; keeping the pressed thin slices at 700 to 750° C. for 3 to 4 hours, and cooling the mixture to room temperature to obtain a nickel-titanium alloy sintered material; placing 200 to 240 parts of the nickel-titanium alloy sintered material into a ball mill, adding an ethanol solution with a mass concentration of 80%, and grinding the mixture for 10 to 12 hours; and drying the mixture at 105 to 110° C. for 2 to 4 hours to obtain a porous nickel-titanium powder.
6. The method for preparing a biological vascular stent material according to claim 1, characterized in that: The method for preparing exosomes in step S2 includes: thawing the plasma in a water bath, centrifuging at room temperature for 20 to 25 minutes to remove residual debris, transferring the supernatant to a centrifuge tube, and storing it on ice to obtain a plasma sample; by weight, adding 0.75 to 0.80 parts of phosphate buffer to 15 to 20 parts of the plasma sample and vortexing to mix evenly, then adding 0.45 to 0.50 parts of exosome extraction reagent and mixing evenly, standing at 4°C for 20 to 30 minutes, and then centrifuging for 5 to 10 minutes, removing the liquid to obtain the precipitate at the bottom of the tube, which is the exosome.
7. The method for preparing a biological vascular stent material according to claim 1, characterized in that: The conditions for the coaxial electrospinning in step S3 are: voltage of 16-22 kV, temperature of 25-30° C., humidity of 40-60%, and receiving distance of 20-25 cm.
8. The method for preparing a biological vascular stent material according to claim 1, characterized in that: The post-treatment in step S4 includes: soaking the composite material in a calcium salt solution with a mass concentration of 2-4% for 30-60 minutes, washing with deionized water after soaking, and drying to obtain a biological vascular stent material.
9. The method for preparing a biological vascular stent material according to claim 8, characterized in that: The calcium salt is selected from any one or a combination of at least two of calcium chloride, calcium lactate and L-calcium gluconate.
10. A biological vascular stent material, characterized in that: Prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A medical vascular stent material and its preparation method
CN113274561B
Cited By
Drug targeted slow release method of degradable stent after hypospadias
CN121130186A